Pengembangan Model Rapid Application Development (RAD) dalam Aplikasi E-Voting Pemilihan Bakal Calon Rektor saat Masa Pandemi Covid 19 - Limbong, Tonni; Sitorus, Lamhot; Sitohang, Oloan (MEANS (Media Informasi Analisa dan Sistem), 2020)
The Catholic University of Santo Thomas conducts the election of the Chancellor by all lecturers and educational staff as well as the Higher Education Senate, by deliberation and voting to elect candidates for the chancellor (lecturers who have met certain qualifications). The implementation system for selecting Candidate Chancellors from its establishment until the 2016-2020 period is still using a manual / conventional system where this system is impossible to implement because the Covid-19 Pandemic period has not ended. Enforcement of Large-Scale Social Restrictions, a regulation issued by the Ministry of Health in the figures for the Acceleration of Handling of COVID-19 recorded in the Minister of Health Regulation No.9 of 2020 restricts the movement of humans to carry out their daily tasks. Rapid Application Development (RAD) as an alternative to the System Development Life Cycle is often used to overcome delays that occur when using conventional methods and is used to build applications to solve these problems. The test results illustrate that there are 115 people (50%) from a total of 230 lecturers and staff of Unika Santo Thomas who are interested / participating in testing the application. On the day of the election, the prospective chancellor indicated that the total number of voters was 230 people, with details of participating as many as 166 people (72.17%) and not exercising their voting rights as many as 64 people (27.83%). This shows an improvement compared to the time of testing.